Goddess, Corporeality and Nature: Study of Ecofeminist Spiritualism - Arivia, Gadis (Jurnal Perempuan, 2014)
This paper investigates the alternative spirituality based on ecofeminism, meaning excavating the feminine spirituality before the birth of monotheism. Feminine spirituality exposed the female god, that is Goddess even before the pre-(his)tory. Faith on the existence of Goddess were not only existed within the Egypt, Greek, and the West but also in ancient Indonesia. Ecofeminist spirituality connected the spirit of the Nature, Wo-men corporeality and female sexuality.